2001
DOI: 10.1128/aac.45.8.2269-2275.2001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cefotaximase (CTX-M-16) with Increased Catalytic Efficiency Due to Substitution Asp-240→Gly

Abstract: Three clinical strains (Escherichia coli Rio-6, E. coli Rio-7, and Enterobacter cloacae Rio-9) collected in 1996 and 1999 from hospitals in Rio de Janeiro (Brazil) were resistant to broad-spectrum cephalosporins and gave a positive double-disk synergy test. Two bla CTX-M genes encoding ␤-lactamases of pl 7.9 and 8.2 were implicated in this resistance: the bla CTX-M-9 gene observed in E. coli Rio-7 and E. cloacae Rio-9 and a novel CTX-Mencoding gene, designated bla CTX

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
122
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 38 publications
4
122
1
7
Order By: Relevance
“…Clinical isolates of Proteus mirabilis, C. amalonaticus, E. cloacae and E. aerogenes collected from hospitals in Rio de Janeiro (Brazil) also demonstrated bla CTX-M-2 (Bonnet et al 2000, Bonnet et al 2001. In South America, the bla CTX-M-2 appears to be dominant in Argentina (Quinteros et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical isolates of Proteus mirabilis, C. amalonaticus, E. cloacae and E. aerogenes collected from hospitals in Rio de Janeiro (Brazil) also demonstrated bla CTX-M-2 (Bonnet et al 2000, Bonnet et al 2001. In South America, the bla CTX-M-2 appears to be dominant in Argentina (Quinteros et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In South America, studies from Argentina have shown that bla CTX-M-2 seems to be the most frequent ESBL among Enterobacteriaceae (Quinteros et al 2003). In the Brazilian Southeast Region, bla CTX-M genes were identified in E. coli, Citrobacter amalonaticus, Enterobacter aerogenes and Enterobacter cloacae (Bonnet et al 2000, 2001, Minarini et al 2007), but bla CTX-M was only recently detected in K. pneumoniae (Do Carmo et al 2008, Garcia et al 2008. In this paper we describe the first detection of bla CTX-M genes and class 1 integrons in clinical isolates of K. pneumoniae from the Northeast of Brazil.…”
mentioning
confidence: 99%
“…A new family of ESBLs, CTX-M, has emerged over recent years, especially in E. coli. This family has become one of the most important families of ESBL enzymes in many countries [28][29][30] . CTX-M ß-lactamases are the predominant type of ESBLs in Europe and South America 29,31 , including Brazil 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most of the CTX-M producers display levels of resistance to cefotaxime significantly higher than those to ceftazidime. However, the classical phenotype of resistance conferred by CTX-M ␤-lactamases is not universal among all CTX-M producers, since many factors, including production of additional ␤-lactamases (1) or mutations altering the substrate specificity of CTX-M enzymes (8,21,33), can mask their presence. Therefore, the phenotype of resistance to ␤-lactams may suggest the presence of CTX-M enzymes, but this is not a completely reliable approach.…”
mentioning
confidence: 99%